STUDENTS' AND TEACHERS' ATTITUDES REGARDING LITERARY TEXTS (WITH EMPHASIS ON THE TEXTS CONTAINING THE DESCRIPTIONS OF NATURE) IN ELEMENTARY SCHOOLS WITH A CURRICULUM IN THE SLOVAK LANGUAGE - Daniela M. Marčoková; Jarmila A. Hodoličová (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2014)
<!-- p { margin-bottom: 0.1in; line-height: 120%; } --> Nowadays, when students seem to read books less often, textbooks are in many cases becoming the only books that bring the students in contact with literature. Taking into consideration the alienation, the busy style of life of today's people and the pursuit of material wealth as the primary goals in life, a textbook should, apart from having an aesthetic function, promote real life values; the texts should above all have an educational infl uence. We are interested in whether students are able to understand the educational messages of the texts by themselves, or if they need the help of a teacher. This research is directed towards analyzing the attitudes of students and their teachers regarding the texts found in textbooks, particularly those containing the descriptions of nature. The results obtained can be used for the improvement of the educational practice in elementary schools in terms of the selection of literary texts for future textbooks written in the Slovak language in Serbia.